Western diet augments metabolic and arterial dysfunction in a sex-specific manner in outbred, genetically diverse mice - Zheng, Xiangyu; Li, Zhuoxin; Berg Sen, Jennifer; Samarah, Luaye; Deacon, Christina S.; Bernardo, Joseph; Machin, Daniel R. (Frontiers in Nutrition, 2023)
Western diet (WD), characterized by excess saturated fat and sugar intake, is a major contributor to obesity and metabolic/arterial dysfunction in humans. However, these phenotypes are not consistently observed in traditional inbred, genetically identical mice. Therefore, we sought to determine the effects of WD on visceral adiposity and metabolic and arterial function in UM-HET3 mice, an outbred, genetically diverse strain of mice. Male and female UM-HET3 mice underwent normal chow (NC) or WD for 12 weeks. Body mass and visceral adiposity were higher in WD compared to NC (P<0.05). Female WD mice had greater visceral adiposity than male WD mice (P<0.05). The results of glucose and insulin tolerance tests demonstrated that metabolic function was lower in WD compared to NC mice (P<0.05). Metabolic dysfunction in WD as was driven by male mice, as metabolic function in female WD mice was unchanged (P>0.05). Systolic blood pressure (BP) and aortic stiffness were increased in WD after 2 weeks compared to baseline and continued to increase through week 12 (P<0.05). Systolic BP and aortic stiffness were higher from weeks 2-12 in WD compared to NC (P<0.05). Aortic collagen content was higher in WD compared to NC (P<0.05). Carotid artery endothelium dependent dilation was lower in WD compared to NC (P<0.05). These data suggest sex-related differences in visceral adiposity and metabolic dysfunction in response to WD. Despite this, arterial dysfunction was similar in male and female WD mice, indicating this model may provide unique translational insight into similar sex-related observations in humans that consume WD.